Peer coaching : a means of assisting beginning teachers - George, David Earl; University of Lethbridge. Faculty of Education (Lethbridge, Alta. : University of Lethbridge, Faculty of Education, 1989, 1989)
92 leaves 29 cm. This study was designed to provide important feedback to the Fort McMurray Catholic School System regarding the nature and effectiveness of a Pilot Teacher Peer Coaching Project which has been implemented to make the induction year a more positive experience for beginning teachers. It was hoped that the study will contribute to the growing body of literature on teacher mentorship as a means of providing support to novice teachers by focussing on the nature, features and prerequisites of effective peer coaching. The study focussed on the perceptions, thoughts and feelings of the nine trained peer coaches regarding the nature of effective peer coaching, the types of assistance given by these mentors to beginning teachers, and ways of making peer coaching projects more effective. The perceptions of a number of beginning teachers were sought in order to corroborate the data gathered from the peer coaches. The first year teache~s were questioned about their needs as inductees to the profession, the forms of assistance they received and the effectiveness of that assistance. The study was qualitative in nature and attempted to construct meaning from what the peer coaches expressed about their work with beginning teachers and what the novice teachers expressed about their year of induction. Data were collected through structured interviews using field notes, written surveys, and direct observation. In general terms, the study found that the peer coaching pilot project was very effective in making the induction year more positive and in providing guidance, counsel and resources to beginning teachers. Furthermore, the peer coaches indicated that there are a number of benefits for them as mentors in such an endeavor. The findings also provide information about the nature and prerequisites of effective peer coaching, and indicate some apparent deficiencies in practice which may need to be addressed to enhance the effectiveness of such work.